Mills_data_final_2018 - Mills, L. Scott; Bragina, Eugenia V.; Kumar, Alexander V.; Zimova, Marketa; Lafferty, Diana J.R.; Feltner, Jennifer; Davis, Brandon M.; Hacklander, Klaus; Alves, Paulo C.; Good, Jeffrey M.; Melo-Ferreira, Jose; Dietz, Andreas; et al. (Dryad Digital Repository, 2018)
This is the data used to build models predicting the probability of winter white for each species across their range. It is needed to run the R script. See README file for column descriptions and more information.